Protecting Against Labour Market Risk: Employment Protection or Unemployment Benefits? - Tito Boeri; Jose Ignacio Conde-Ruiz; Vincenzo Galasso (Institute for the Study of Labor (IZA), 2003)
We document the presence of a trade-off between unemployment benefits (UB) and employment protection legislation (EPL) in the provision of insurance against labour market risk. The mix of quantity restrictions and price regulations adopted by the various countries would seem to correspond to a stable politico-economic equilibrium. We develop a model in which voters are required to cast a ballot over the strictness of EPL and over the generosity of UB. Agents are heterogeneous along two dimensions: employment status – there are insiders and outsiders – and skills – low and high skills. We show that if there exists a majority of low-skill insiders, the voting game has a politico-economic equilibrium with low UB and high EPL; otherwise, the equilibrium features high UB and low EPL. Another testable implication of the model is that a larger share of elderly workers increases the demand for EPL. Panel data on institutions and on the age and educational structures of the populations are broadly in line with our results. We also find that those favouring EPL over UB in a public opinion poll carried in 2001 in Italy have precisely the same characteristics predicted by our model.
Keywords: D72; J65; J68; 330; employment protection; unemployment insurance; political equilibria; Arbeitsrecht; Kündigungsschutz; Arbeitslosenversicherung; Public Choice; Insider-Outsider-Modell; Qualifikation; Theorie; Schätzung; Italien